A systematic review of randomised controlled trials of the effects of digital health interventions on postpartum contraception use. Issue 1 (28th October 2022) - Sze, Yik Yan; Berendes, Sima; Russel, Sophie; Bellam, Laura; Smith, Chris; Cameron, Sharon; Free, Caroline J
Abstract : Background: Digital health interventions (DHI) have been used to enhance the uptake of postpartum contraception and reduce unmet contraception needs. We conducted a systematic review of the effectiveness of DHI on postpartum contraceptive use and repeated pregnancy. Method: We searched MEDLINE, Embase, Global Health, CINAHL and Cochrane CENTRAL (January 1990–July 2020). Randomised controlled trials (RCTs) of DHI promoting contraception among pregnant or postpartum women were included. Two researchers screened articles and extracted data. We assessed the risk of bias, certainty of evidence (CoE) and conducted meta-analyses following Cochrane guidance. Results: Twelve trials with 5527 women were included. Interventions were delivered by video (four trials), mobile phone counselling (three trials), short message services (SMS) (four trials) and computer (one trial). During pregnancy or the postpartum period, mobile phone counselling had an uncertain effect on the use of postpartum contraception (risk ratio (RR) 1.37, 95% CI 0.82 to 2.29, very low CoE); video-based education may moderately improve contraception use (RR 1.48, 95% CI 1.01 to 2.17, low CoE); while SMS education probably modestly increased contraception use (RR 1.12, 95% CI 1.01 to 1.23, moderate CoE). Mobile phone counselling probably increased long-acting reversible contraception (LARC) use (RR 4.23, 95% CI 3.01 to 5.93, moderate CoE). Both mobile phone counselling (RR 0.27, 95% CI 0.01 to 5.77, very low CoE) and videos (RR 1.25, 95% CI 0.24 to 6.53, very low CoE) had uncertain effects on repeated pregnancy. Conclusions: During pregnancy or in the postpartum period, videos may moderately increase postpartum contraception use and SMS probably modestly increase postpartum contraception use. The effects of DHI on repeated pregnancy are uncertain. Further well-conducted RCTs of DHI would strengthen the evidence of effects on contraception use and pregnancy.